Discriminant Function Analysis for Gender Determination Using Maxillary Sinus Volume and Index: A Cone-Beam Computer Tomography Study - Jaafar, Nuraddeen Ibrahim; Katta, Prashanth Kumar (European Journal of General Dentistry, 2025)
The purpose of the study was to establish baseline values for maxillary sinus volume (MSV) and maxillary sinus index (MSI) among a population of Saudi adults and to test the accuracy of using MSV and MSI for gender determination among the study samples.Two hundred and seventy-five cone-beam computer tomographic (CBCT) images of adults that satisfy the study criteria were recruited as the study samples. The CBCT images were obtained from the patients' records in the CBCT database of the dental clinic of King Faisal University, Al-Ahsa, Saudi Arabia. Maxillary sinus height (H), width (W), and depth (D) were measured from the coronal, axial, and sagittal image views using a vision iCAT software. The MSV and MSI were obtained by the mathematical formula MSV = H*W*D*0.33 in cm3 and MSI = W/H. Data was analyzed using SPSS software, and a discriminant function test was used to test for gender determination.Mean MSV was 12.67 mm ± 3.46, and mean MSI was 0.88. No statistically significant difference was observed between the right and left (p > 0.05). There was strong gender dimorphism in both MSV and MSI in the samples. Males have statistically higher mean (p = 0.001) MSV and MSI (p = 0.002). The discriminant function test shows an overall gender predictive accuracy of 84% when MSV was used for gender determination and 77% when MSI was used.Both MSV and MSI are good predictors for gender determination, but MSV is superior and has higher accuracy.
Keywords: cone-beam computer tomography; gender dimorphism; gender determination; maxillary sinus index; maxillary sinus volume